2008
DOI: 10.1097/jes.0b013e31817be928
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone Effects on Body Fluid Regulation

Abstract: In young women, estradiol and progesterone primarily control reproduction, but they also affect fluid regulation. Estradiol lowers the operating point for osmoregulation of arginine vasopressin and thirst and increases plasma volume. Although total body water and sodium content are only mildly affected, data presented in this article suggest that reproductive hormones alter homeostatic set points for body fluid and tonicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 31 publications
6
128
1
1
Order By: Relevance
“…This is in accordance with the GenSalt study, performed in a large number of participants in rural China [6]. Perhaps, this must not be a surprise given the complex effects of sex hormones on body fluid regulation [11], and greater aldosterone response in women [12]. Also in the Dietary Approaches to Stop Hypertension (DASH) salt study, women had a greater BP response to reduction of dietary salt while on DASH diet [13].…”
Section: Discussionsupporting
confidence: 83%
“…This is in accordance with the GenSalt study, performed in a large number of participants in rural China [6]. Perhaps, this must not be a surprise given the complex effects of sex hormones on body fluid regulation [11], and greater aldosterone response in women [12]. Also in the Dietary Approaches to Stop Hypertension (DASH) salt study, women had a greater BP response to reduction of dietary salt while on DASH diet [13].…”
Section: Discussionsupporting
confidence: 83%
“…In addition to testosterone, other sex steroid hormones such as estrogen and progesterone have also been shown to affect kidney H 2 O handling. Androgen, estrogen, and progesterone receptors have been reported to be expressed in the kidney, [19][20][21][22] suggesting that kidney functions are controlled by sex steroids. Estrogen was found to directly affect AQP expression in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, central actions of estrogen influenced body fluid regulation [53]. Stachenfeld et al [54] reported that estrogen therapy retained body water in menopausal women to avoid dehydration. Thus, estradiol lowered the operating point for osmoregulation of arginine vasopressin and thirst and increased plasma volume [55].…”
Section: Discussionmentioning
confidence: 99%